Bridging the transition gap: the role of practical career education in enhancing independent living skills for adolescents with developmental disabilities in Vietnam - Dao Thi Thu Thuy; Nguyen Thi Quynh Hoa; Nguyen Thi Kim Hoa; Nguyen Thi Huyen; Nguyen Thi Phuong Hoa (International Journal of Evaluation and Research in Education (IJERE), 2026)
The transition to adulthood for adolescents with developmental disabilities (DD) in Vietnam is fraught with challenges, marked by a gap between rights-based policies and practical support. This study addresses the critical need to identify effective interventions for enhancing their independent living skills (ILS). Adopting the social cognitive career theory (SCCT) framework, we conducted a quantitative survey with 458 special education teachers and parents to evaluate the impact of three career education (CE) dimensions: practical teaching methods, teacher competence, and experiential environment. Multiple regression analysis revealed that practical teaching methods were the most significant predictor of socio-adaptive competence (β=.48). A key finding was the “will-skill” discrepancy, where students’ high motivation (M=3.35) contrasted with their limited functional skills (M=3.18). We conclude that in resource-constrained contexts like Vietnam, hands-on, task-based instruction is paramount. The study provides empirical evidence for policymakers to prioritize practical vocational training over theoretical approaches to effectively bridge the gap between students’ aspirations and their actual capabilities, fostering genuine autonomy.